Exploring the Potential of SGLT-2 Inhibitors in Cancer Treatment: Mechanisms, Preclinical Findings, and Clinical Implications - Sokołowska, Aldona; Fikas, Klaudia; Chwaliszewski, Kamil; Samuła, Sebastian; Mazur, Michał; Waz, Dorota; Szarłowicz, Jakub; Goliszek, Zofia; Sobek, Karolina Łucja; Tabin-Barczak, Wiktoria (Quality in Sport, 2025)
Introduction Sodium-glucose co-transporter 2 (SGLT-2) inhibitors, originally developed for the treatment of type 2 diabetes, have recently attracted attention for their potential applications in oncology. Their potential to modulate tumor metabolism and enhance responses to cancer therapies is an area of increasing interest. Aim of the study This review aims to explore the emerging role of SGLT-2 inhibitors in cancer treatment, focusing on their mechanisms of action, preclinical findings, and early clinical evidence. By understanding the potential of these agents to alter tumor metabolism and the immune microenvironment, we can evaluate their therapeutic value in cancer management. Material and Methods Data were gathered from peer-reviewed articles, clinical trials, and ongoing research on the use of SGLT-2 inhibitors in combination with chemotherapy, immunotherapy, and other cancer treatments. Description of the state of knowledge Preclinical studies suggest that SGLT-2 inhibitors can alter cancer cell metabolism by limiting glucose availability, potentially impeding tumor growth. These agents have demonstrated promise in models of breast, prostate, and pancreatic cancers, reducing cell proliferation and enhancing the efficacy of standard cancer treatments. Conclusions SGLT-2 inhibitors represent a novel therapeutic strategy in oncology, with potential to improve outcomes in combination with traditional therapies. However, more extensive clinical trials are required to validate their effectiveness, optimize treatment regimens, and better understand their safety profiles in cancer patients.